Rates of Never Receiving Cervical Cancer Screening Among US Women, 2005-2023 - Kalyani Sonawane; Haluk Damgacioglu; Trisha L. Amboree; Marvella E. Ford; Ketki N. Borse; Brian Orr; Gweneth Lazenby; Ana Patrica Ortiz; Ashish A. Deshmukh (JAMA Network Open, 2026)
This cross-sectional study examines trends in the prevalence of never having been screened for cervical cancer from 2005 to 2023 and assesses trends in cervical cancer incidence by age and stage at diagnosis to determine whether incidence patterns correspond with trends in nonscreening.